In vitro Propagation of Holarrhena antidysenterica Wall., Wedelia chinensis (Osb.) Merr. and Woodfordia fruticosa (L.) Kurz. - Islam, S.A.M. Nurul; Banik, Haradhan; Tarek, Saiful Alam M.; Rahman, Mahbubur (Plant Tissue Culture and Biotechnology, 2010)
Key words: Medicinal plant, Holarrhena antidysenterica, Wedelia chinensis, Woodfordia fruticosa, In vitro cloning, Multiple shoot D.O.I. 10.3329/ptcb.v19i2.5443 <span style="font-size: 9pt; font-family: Palatino; mso-bidi-language: AR-SA; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-size: 12.0pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">Plant Tissue Cult. & Biotech. 19(2): 253-255, 2009 (December) <span style="font-size: 10pt; font-family: Palatino; mso-bidi-language: AR-SA; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">- Short communication